History of Pesticide Exposure as a Risk Factor for Spontaneous Abortion in Female Farmers in Bandungan District, Semarang Regency - Qomariyah, Siti; Setiani, Onny; Suhartono, Suhartono (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abortion is the termination of pregnancy before the fetus can live outside the womb, namely the age of fewer than 20 weeks of gestational age with a fetal weight of fewer than 500 grams (The prevalence of spontaneous abortion throughout the world varies, but generally reaches 0.3%. Abortion rates among farmer’s exposure to pesticides are as much as 9%. Several studies report that women who have exposure to pesticides or work in the agricultural sector are at risk of spontaneous abortion. The study uses case-control, involving 42 case group respondents and 42 control group respondents in Bandungan District. The variables studied were a history of pesticide exposure (the degree of pesticide exposure, the practice of pesticide use, the practice of storing pesticides, the type of pesticide) with the incidence of spontaneous abortion. Analysis using the Chi-square test. The results showed an association between the practice of storing pesticides with spontaneous abortion (p value = 0.030, OR = 3.301 CI 95%), organophosphate pesticide types (p value = 0.038, OR = 3.210 CI 95%), carbamate pesticides (p value = 0.008, OR = 0.200 CI 95%).